Alienation and the factory worker / Choong Chooi Lian - Choong , Chooi Lian (1977)
This is a study of the alienation of factory workers from their work. The study focuses on the aspects of powerlessness, meaninglessness, self engagement and social alienation and how each of these contribute of the feelings of alienation. The works of this study were come from a factory in Petaling Jaya which produce drinks and toiletries.